Precariat as a social class: the features of scientific discourse - Гоженко, І. С. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
This article identifies the features of the theoretical understanding of the precariat as a new social class. The work of world and domestic thinkers, such as G. Standing, U. Beck, Z. Bauman, I. Kononov, Zh. Toshchenko, is analyzed. The article defines the precariate, describes the causes of its occurrence, as well as the structure and characteristics. The danger of the precariate as a social class is that elites can use it to achieve their narrowly individual goals.